2020
DOI: 10.1108/aeds-05-2020-0081
|View full text |Cite
|
Sign up to set email alerts
|

Shifting perceptions of same-sex marriage in Taiwan: who changed their mind after legalization?

Abstract: PurposeThis article addresses Taiwanese public opinion on same-sex marriage, connecting it to the 2020 general election.Design/methodology/approachOriginal survey data are combined with analysis of the existing literature and 2020 election results.FindingsOriginal survey data find that nearly one in five respondents have changed their views on same-sex marriage since its legalization, with most of those who have changed their views more opposed to legalization than before. However, this shift and its related s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Notably, the legalization of SSM in Taiwan does not suggest widespread societal support for same-sex relationships but rather is a result of years of political negotiations and advocacy [ 1 ]. A study has documented a marginal shift in the public attitudes towards SSM since the passage of legislation [ 2 ]. However, the legalization of SSM assumes vital implications for sexual minority individuals (i.e., lesbian, gay, and bisexual, LGB).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the legalization of SSM in Taiwan does not suggest widespread societal support for same-sex relationships but rather is a result of years of political negotiations and advocacy [ 1 ]. A study has documented a marginal shift in the public attitudes towards SSM since the passage of legislation [ 2 ]. However, the legalization of SSM assumes vital implications for sexual minority individuals (i.e., lesbian, gay, and bisexual, LGB).…”
Section: Introductionmentioning
confidence: 99%
“…748 neither legally recognize the ability of a same-sex spouse to adopt his or her partner’s non-biological children nor the ability to register transnational same-sex marriages in cases where a partner is from a country where same-sex marriage is not legalized, showing that there is still discrimination in how same-sex marriage is treated [ 22 , 23 ]. A study on 502 Taiwanese people conducted in December of 2019 found that 19.3% of participants have changed their views on same-sex relationship since its legalization, with most of those who have changed their views more opposed to legalization than before [ 24 ].…”
Section: Introductionmentioning
confidence: 99%